CUKUL ESTATE: Perkembangan dan Dampaknya Bagi Buruh Petik Tahun 1972-2007 - Temi Setiabudi (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2017)
The plantation of PT. Tatar Anyar Indonesia (Cukul Estate) is one of the many tea plantations in West Java. In the next developtment tea plantations has a long history in the distribution of tea plantations in Indonesia, from the Netherlands and will be followed by other businessmen from various countries in accordance with the existing historical period. Especially for plantation Cukul, occur several times of ownership. Starting from 1948-1965 managed by the British company under the name P T Land (Pemanukan and Tjiasem Land), in 1965-1972 through the process of nationalization of the British-owned plantation company has handed over its management to Subang Plantation Company, from 1972 to 2007 through a Government Regulation No.3 / 1971 Cukul plantations managed by PT. Tatar Anyar Indonesia through the joint venture between the foreign company (UK) with the national private. The existence of Cukul plantations give effect to the economy of surrounding communities through employment. In this case, tea pickers become an important part in the process of tea production. For the farmer, policies aimed at to increase the welfare through the provision of facilities such as health, education and other social security (holiday allowance) for the workers’ prosperous life. But the reality is very alarming, many of the workers less prosperous, still lacking attention to child labor, not all family members get health care.